2018
DOI: 10.1093/mnras/sty2943
|View full text |Cite
|
Sign up to set email alerts
|

The intraday variations of the polarization vector direction in radio source S5 0716+714

Abstract: The bright radio source S5 0716+714, that is usually classified as BL Lac object, is one of the most intensively studied. S5 0716+714 demonstrates extremely peculiar properties such as the shortest time-scale of optical and polarimetric variations observed in blazars. In given paper, the results of 9-hour polarimetric monitoring of S5 0716+714 with the ∼70-second resolution carried out by the 6-m telescope BTA of SAO RAS, are presented. The observation data analysis reveals the variability both in total and po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…Wavelet analysis shows the period of light variations of the object to be 76±10 minutes. The agreement between the period of light variations and that of the variations of the polarization vector are totally consistent with the result that we earlier obtained based on observations made with the 6-m telescope of the Special Astrophysical Observatory of the Russian Academy of Sciences [14]. Thus the observations mentioned above show that the task of the polarimetry of relatively bright (about 13-14 m ) starlike objects can be successfully addressed with the "StoP" instrument and the accuracy of both photometry and polarimetry are on a par with those of the results obtained with the 6-m telescope.…”
Section: Observationssupporting
confidence: 92%
See 2 more Smart Citations

Stokes-polarimeter for 1-meter telescope

Afanasiev,
Shablovinskaya,
Uklein
et al. 2021
Preprint
“…Wavelet analysis shows the period of light variations of the object to be 76±10 minutes. The agreement between the period of light variations and that of the variations of the polarization vector are totally consistent with the result that we earlier obtained based on observations made with the 6-m telescope of the Special Astrophysical Observatory of the Russian Academy of Sciences [14]. Thus the observations mentioned above show that the task of the polarimetry of relatively bright (about 13-14 m ) starlike objects can be successfully addressed with the "StoP" instrument and the accuracy of both photometry and polarimetry are on a par with those of the results obtained with the 6-m telescope.…”
Section: Observationssupporting
confidence: 92%
“…The main task of the "StoP" instrument is to perform high-precision polarimetric observations of starlike objects, and in this sense are unparalleled among attachable equipment for Zeiss-1000 telescope. The technique of the measurement of the polarization of point-like sources with an accuracy of 0.1% was successfully used on the 6-m telescope of the Special Astrophysical Observatory of the Russian Academy of Sciences equipped with SCORPIO-2 instrument [14], where observations involved the use of an analyzer similar to that incorporated in "StoP"-double Wollaston prism WOLL-2. To test the technique of observations we decided to repeat observations of the blazar S5 0716+714.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation

Stokes-polarimeter for 1-meter telescope

Afanasiev,
Shablovinskaya,
Uklein
et al. 2021
Preprint
“…Optical radiation is assumed to be synchrotron. Despite the fact that one of the advantages of the TEMZ model is that it provides an explanation for the observed rotation of the electric vector in the wave, Shablovinskaya & Afanasiev (2019) showed that on a time scale of several hours the changes in the electric vector direction in the wave observed for S5 0716+714 correspond to the motion of a particle in the precessing helical magnetic field. The TEMZ model was applied to interpret the IDV flares of the blazar S5 0716+714 (Bhatta et al 2013;Xu et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important for the studies of ultra-fast variations. The results of the first attempts of such observations for one of the blazars (S5 0716+714) were published recently [17].…”
Section: Consideration Of Tablementioning
confidence: 99%